2019
DOI: 10.3390/ijms20164010
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Negative Affective Dimension of Pain: Focus on Selected Neuropeptidergic System Contributions

Abstract: It is well known that emotions can interfere with the perception of physical pain, as well as with the development and maintenance of painful conditions. On the other hand, somatic pain can have significant consequences on an individual’s affective behavior. Indeed, pain is defined as a complex and multidimensional experience, which includes both sensory and emotional components, thus exhibiting the features of a highly subjective experience. Over the years, neural pathways involved in the modulation of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 129 publications
0
6
0
Order By: Relevance
“…Moreover, the MCLS seems to be involved in the modulation of negative affective states occurring in pain conditions. (Caputi et al, 2019;Jesús David Lorente et al, 2020;Massaly et al, 2019) Thereby, we measured the mRNA levels of pDYN and KOR in the NAc and the Amy by qRT-PCR together with its protein expression in these areas by ELISA and western blot.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the MCLS seems to be involved in the modulation of negative affective states occurring in pain conditions. (Caputi et al, 2019;Jesús David Lorente et al, 2020;Massaly et al, 2019) Thereby, we measured the mRNA levels of pDYN and KOR in the NAc and the Amy by qRT-PCR together with its protein expression in these areas by ELISA and western blot.…”
Section: Resultsmentioning
confidence: 99%
“…These opioid neuropeptides and their corresponding receptors are widely distributed across the neuraxis, and, in particular, in pain pathways [ 23 ]. Additionally, evidence showed that they also participate in the control of many different functions, such as stress responses, depression, anxiety, reward/aversion behavioral response, gastrointestinal transit, and the neuroendocrine and immune functions [ 26 28 ]. Upon agonist activation, either endogenous or exogenous, the inhibitory G proteins (Gαi–Gαo) dissociate and subsequently engage a variety of effectors that induce neuronal depression [ 24 ], through the inhibition of adenylate cyclase and ion channel modulation [ 29 , 30 ].…”
Section: Endogenous Opioid Systemmentioning
confidence: 99%
“…Overall ANOVA revealed a significant effect of strain on the pN/OFQ gene expression [F (1,20) = 16.17, p = 0.0007]; no significant effect of EtOH drinking [F (1,20) = 2.510, p = 0.1288, n.s.] and of strain × EtOH drinking interaction [F (1,20) = 2.731, p = 0.1140, n.s.]…”
Section: Pn/ofq Expressionmentioning
confidence: 99%
“…Moreover, we decided to expand our analysis to the corticotropin-releasing factor (CRF)–CRF receptor 1 (CRF1R) as it is tightly linked to the regulation of the above mentioned opioidergic mechanisms. In fact, it is well known that both CRFergic and DYNergic transmissions mediate stress response and contribute to the expression of negative reinforcement [ 18 , 19 , 20 , 21 ]. Whereas, activation of NOP by N/OFQ results in a functional CRF antagonism and mediates anti-stress responses [ 19 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation